Genetic Characteristics and Research Progress of Feline Coronavirus - TAO Lingyun (Shiyan dongwu yu bijiao yixue, 2024)
Feline coronavirus (FCoV) is classified into two biotypes: feline infectious peritonitis virus (FIPV) and feline enteric coronavirus (FECV). FIPV and FECV might evolve and mutate via genetic recombination and mutation, leading to novel subtypes and variants. This study examined the genomic structure and biological subtyping of FCoV, analyzed the infection characteristics of FIPV and FECV, and investigated the mechanisms of FECV transforming into FIPV. The findings revealed that while their genome structures were fundamentally similar, differences in their ability to efficiently infect monocytes/macrophages significantly influenced their pathogenicity and transmission characteristics, with FIPV exhibiting higher virulence. Moreover, the analysis of the open reading frames (ORF)3/7 as well as the N/S sequences of FIPV indicated that its non-structural proteins were associated with modulation of the host immune system. These proteins enabled immune evasion, leading to more severe disease. The genomic variability of FCoV constitutes an important foundation for studying the pathogenicity and epidemiology of FIPV and FECV, and offers references for virus detection and drug development.